Ward management and Empowerment of Society Through the Development of Potential Tourism in the South Singkawang Environment - Nindy Citroresmi Prihatiningtyas; fitri - fitri; Eti Sunarsih; Eka Murdani; Nurul Husna; Rien Anitra (International Journal of Public Devotion, 2019)
The activities dedicated to the community for environmental management and empowerment of communities through the development of tourism potential are implemented by partnering up the PKK suport team, the domestic chairman and the weal community.  It aims to give understanding, khowledge, and empower societies to realize a society conscious of a tourist environment that must be maintained and preserved.  These environmental management and community empowerment activities are done by methods of speech, discussion, question-and-answer, and demonstration. The benefits of this activity includes; (1) Together people build tourist areas (2) It grows and increases people’s sense of and cares for the beautiful of Batu Burung, (3) To encourage people to participate in the preservation of Batu Burung,  (4) Assisting the goverment program to promote tourist areas aspecially Batu Burung sites that are still not widely known by outside Sedau society, and (5) provides services that can enable visitors to know where Batu Burung is located and provide products fo garbage diposal on Batu Burung Beach..